Desk stories - O'Malley, Kevin, 1961- (Chicago : Albert Whitman, 2011)
Six separate stories tell, in words and cartoons, the surprising history and activities of the ordinary school desk.
History Man -- Trapped! -- It came from within -- Desk time jokes -- Desktec -- Sue Smallton.
Publisher's Weekly
Publisher's Weekly, June 2011
4.0
K-3
K-3
Keywords: Desks -- Juvenile fiction; Cartoons and comics; Desks -- Fiction; Humorous stories; Comic books, strips, etc; Desks -- Fiction; Humorous fiction; Humorous fiction; Picture books for children